Financial Management, Time Management, and Wives’s Subjective Well - Being on Wives Working Full-Time - Hasanah, Uswatun; Silitonga, Mirdat (International Journal of Psychosocial Rehabilitation, 2020)
Most of the management of various household tasks is the responsibility of the wife. This makes wives who work full-time experience their problems, especially in financial management and time management, which affects the wife’s subjective well-being. This study aims to analyze the influence of financial management and time management on personal well-being for wives who work full time. This study used a cross-sectional study design. The study population was women who had husbands and children who worked full time in the Rawamangun village, Pulogadung Regency, DKI Jakarta Province. The research respondents were selected by purposive sampling, with a total sample of 50 wives. Regression results indicate that the factors that influence the subjective well-being of wives are financial management and time management. Therefore, wives who work full-time are expected to improve time management, especially in determining priorities, while in financial management, the wife must make household financial records and ensure valuables are owned by the family so that the wife’s subjective well-being can increase.